Managing The Motivation of Middle Managers And Forms of Reinforcement That Affect Their Commitment: Case Study of Advertising Agency X - Bogna KONODYBA-RORAT (Communications of International Proceedings, 2024)
The aim of this paper is to identify the role and importance of motivating middle managers as a crucial element of human resources management and to highlight the challenges in this area for Advertising Agency X. The first part of the paper defines the term "motivation" and addresses the topics of (internal) intrinsic and (external) extrinsic motivation. It also presents selected motivation theories as well as material and non-material motivators. As part of a case study, pilot research was conducted in Advertising Agency X. The purpose of the research was to determine the role and forms of appreciating employees in managerial roles in the process of motivating them to work. Appreciation from superiors is a key factor in increasing motivation, leading to improved performance and overall job satisfaction. Analysis of the research indicates appropriate reinforcement forms that can be used in motivation management at Advertising Agency X. The paper highlights the fact that managers who can successfully motivate and appreciate their subordinates often achieve better results, cultivate a positive atmosphere in the workplace, and minimize employee turnover. This, in turn, contributes to the stability and long-term success of the organization. Based on the numerous sources referenced in this paper, as well as the conducted research, it has been demonstrated that motivation is a particularly important element of human resources management and requires constant improvement.
Keywords: managers' motivation; motivation management; material and non-material motivators; appreciation